Evaluation of Iron Deficiency Anemia in a Pediatric Clinic in the Dominican Republic - Steven G McKee; Ryan Close; Elizabeth Lowenthal (Ubiquity Press, 2017)
Background Iron deficiency and iron deficiency anemia affect billions of people worldwide. Infants and young children are the most vulnerable. The Niños Primeros en Salud pediatric clinic aims to follow the American Academy of Pediatrics (AAP) recommendation to screen all children at 12 months of age, a vital period for development and the time of greatest risk. Objectives To evaluate the clinic's performance screening for, diagnosing, and treating iron deficiency anemia; and to describe the prevalence and severity of anemia in infants and children attending a perirural clinic in the Dominican Republic. Methods A total of 293 charts were reviewed for hemoglobin tests performed between 9 and 15 months of age. If a hemoglobin screening was performed, then sociodemographic characteristics, medical history, and laboratory data were collected. If blood tests revealed anemia, then the presence or absence of documented anemia diagnosis as well as the presence or absence of documented provision of iron therapy were recorded. Findings Less than one-third (87, 29.7%) of patients had a documented hemoglobin test performed in this age range. Of these, 89.6% indicated anemia and nearly half (48.6%) revealed moderate anemia. One-third (34%) of hemoglobin results revealing anemia were not accompanied by a documented diagnosis. The vast majority (86.5%) of results indicated microcytosis, yet just more than half (50.8%) of anemic patients received iron therapy. Conclusions Many children at the clinic were not screened for iron deficiency anemia during the period of highest risk. In the participants screened, iron deficiency anemia was underdiagnosed and often untreated. Anemia is a significant burden in this community-one demanding reliable screening and universal supplementation.